Inclusion in the university: Who assumes responsibility? A qualitative study - Solís Grant, María José.; Bretti López, María José.; Espinoza Parçet, Camila.; Pérez Villalobos, Cristhian.; Rodríguez Núñez, Iván.; Pincheira Martínez, Cristian.; Sepúlveda Carrasco, Cristóbal Rodrigo. (Public Library of Science, 2023)
Society challenges higher education institutions and their members to generate inclusive communities to enable the full development of all members. This study aims to analyze who is responsible for generating inclusion according to community members from a traditional Chilean University. We carried out qualitative research based on the Grounded Theory. We collected data through focus group and semi-structured Interviews, involving 14 undergraduate students, two post-graduate students, 17 faculty members, five non-teaching staff members, and nine executives officers. All of thembelonging to the three campuses of the University. We analyzed data using ATLAS.ti 7.5.7, using the constant comparison method and reaching an axial codification level. From the data analysis, 25 subcategories emerged, grouped into six categories. Later we organized them under the codification paradigm. Results highlighted the perception of the interaction and influence of the social, institutional, and personal fields in the inclusion phenomenon. Also, that inclusive practices must be a responsibility shared among different educational community members.
Keywords: Educación inclusiva